2003
DOI: 10.1063/1.1512774
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, accurate, and direct determination of total lycopene content in tomato paste

Abstract: Lycopene that imparts red color to the tomato fruit is the most potent antioxidant among carotenes, an important nutrient and also used as a color ingredient in many food formulations. Since cooked and processed foods derived from tomatoes were shown to provide optimal lycopene boost, products such as paste, puree, juice, etc. are nowadays gaining popularity as dietary sources. The analysis of lycopene in tomato paste ͑partially dehydrated product prepared by vacuum concentrating tomato juice͒ is carried out u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The first publication on the PT study of carotenoids described the application of an OW sapphire detector for the quantification of lycopene in six tomato pastes [14]; the excitation of the carotenoids was achieved with the c.w. argon-ion laser emitting 20 mW at 502 nm.…”
Section: Pa and Ow Detection Of Carotenoidsmentioning
confidence: 99%
“…The first publication on the PT study of carotenoids described the application of an OW sapphire detector for the quantification of lycopene in six tomato pastes [14]; the excitation of the carotenoids was achieved with the c.w. argon-ion laser emitting 20 mW at 502 nm.…”
Section: Pa and Ow Detection Of Carotenoidsmentioning
confidence: 99%
“…The first research study, the outcome of which indicated the intrinsic feasibility of the PT methods for direct detection of lycopene, described the application of the optothermal window (OW) concept to several tomato purée concentrates (7). Optimization of the experimental setup and improved design of the OW sensor enabled the extension of the measuring range of the OW technique to lower concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the necessity for a reliable and rapid analysis method for carotenoid quantification in vegetable products is recognized in the literature (5,6). Carotenoid analysis in food products may be done by different analytical methods such as high-performance liquid chromatography (HPLC), spectrophotometry, or color evaluation (7,8).…”
Section: Introductionmentioning
confidence: 99%